Knowledge and Experience Related to Community Supported Agriculture and Local Foods among Nutrition Educators. Issue 2 (3rd March 2020) - Seguin, Rebecca A.; McGuirt, Jared T.; Jilcott Pitts, Stephanie B.; Garner, Jennifer; Hanson, Karla L.; Kolodinsky, Jane; Sitaker, Marilyn
ABSTRACT: Improving knowledge and access to local food systems may be a successful approach to improving fruit and vegetable intake. Nutrition educators can play a role in the implementation of local food programming, yet few studies have explored nutrition educators' knowledge, beliefs, and experiences with local foods. The purpose of this qualitative study was to examine nutrition educators' experiences with, knowledge of, and beliefs about local foods, and to elicit ideas on how to integrate education about and access to local food systems into their current work. Nutrition educators were invited participate in a telephone interview (n=20) and focus group (n=17). Questions asked in the interviews and the focus groups were unique but paralleled one another. Interviews and focus groups were audio recorded, transcribed verbatim, and coded in NVivo version 11. Educators' interests in local food was supported through a desire to help local agriculture and the local economy, local food being "a way of life" or part of their culture, and having strong agricultural ties. The majority of educators defined themselves as a local food advocate; however, few had direct experience with Community Supported Agriculture (CSA). Variability across seasons, financial issues, and risk of spoilage were identified as challenges of using seasonal, local foods within programming. Various strategies for promoting local foods and improving local food systems were identified. Understanding educator knowledge, beliefs, and experiences toward local foods can help design programs that may improve educator participant interaction and maximize program impact.